Analisis Kesulitan Siswa Kelas V dalam Menyelesaikan Soal Cerita Matematika pada Materi Bangun Ruang di SD Negeri 96 Palembang - Valentin, Yosi Piona; Tanzimah; Noviati (Pendagogia: Jurnal Pendidikan Dasar, 2023)
This research is motivated by the problems of students who have difficulty in solving math story problems. This study aims to describe what difficulties are experienced by fifth grade students in solving math story problems, especially on the material of geometry. This research method uses qualitative methods. The subjects in this study were students and class V.B teachers of SD Negeri 96 Palembang. Data collection techniques used are in the form of documentation and interviews. The results showed that the difficulties experienced by class V.B students in solving math story problems in geometry materials were based on the factual error category, namely the difficulty in determining what was known and what was asked in the math story problems, the difficulty in focusing on solving math story problems and the difficulty in understanding the problems. math stories; conceptual errors, namely difficulty understanding math story problems, difficulty focusing on math story problems and difficulty performing number operations; operating errors, difficulties in performing multiplication operations, especially if the numbers are in the tens and hundreds, difficulties in performing arithmetic operations, difficulties in performing mixed arithmetic operations and difficulties in performing multiplication operations with decimal numbers; The principle error of difficulty experienced by students is not knowing the spatial formula contained in the problem and difficulties in remembering the spatial formula contained in the problem.